Evaluating Geogrid-Reinforced Pavements with Field-Validated Soil Models under Vehicle Load Dynamics - Tiwari, Aanchal; Shahi, Padma Bahadur; Suwal, Rajan; Tiwari, Ram Chandra; Jha, Prabhat Kumar (Journal on Transportation System and Engineering, 2025)
This study investigates the application of geogrid reinforcement to improve the stress-strain behavior of pavement structures, with the goal of mitigating structural deficiencies and surface distresses. A three-dimensional numerical analysis was conducted using Plaxis software, incorporating both field and laboratory data to evaluate the suitability of various soil material models. The analysis focused on the Arughat–Okhale section of the Midhill Highway to determine the most appropriate model among the linear elastic, Mohr-Coulomb, hardening soil, soft soil, and modified Cam-Clay models. Results indicate that the linear elastic model is applicable for certain conditions, while the hardening soil and soft soil models produce outcomes that closely align with field observations. The Mohr-Coulomb, hardening soil, and soft soil models yielded similar results, whereas the modified Cam-Clay model significantly deviated from both the other models and the field measurements. These findings are based on subgrade soil modeling; applying similarly appropriate models to the other pavement layers could yield results that more accurately reflect field conditions.